2018
DOI: 10.1097/md.0000000000013856
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of early T-cell precursor acute lymphoblastic leukemia

Abstract: Rationale:Early T-cell precursor acute lymphoblastic leukemia (ETP-ALL) is a small subtype of T-cell acute lymphoblastic leukemia with a typical immune-phenotype: lack of T-lineage cell surface markers CD1a and CD8 expression, weak or absent CD5 expression, at least one of the myeloid or hematopoietic stem cell markers. It is characterized by high rate of induction failure and the effective unified treatment strategies are still indeterminate. We present 2 ETP-ALL cases.Patient concerns:A 42-year-old man prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
7
0
3
Order By: Relevance
“…Wang et al reported two cases ETP-ALL, presenting with fever and abnormal hemogram showing blasts, one case presented with lymphadenopathy. 18 LBL cases in a study done by Jain et al presented lymphadenopathy as most common symptom followed by skin involvement, supraclavicular and tonsillar mass. 14 Lymphadenopathy is most prominent presentation in our study mainly seen in non ETP-ALL cases and was not present in ETP-ALL cases.…”
Section: Casementioning
confidence: 96%
“…Wang et al reported two cases ETP-ALL, presenting with fever and abnormal hemogram showing blasts, one case presented with lymphadenopathy. 18 LBL cases in a study done by Jain et al presented lymphadenopathy as most common symptom followed by skin involvement, supraclavicular and tonsillar mass. 14 Lymphadenopathy is most prominent presentation in our study mainly seen in non ETP-ALL cases and was not present in ETP-ALL cases.…”
Section: Casementioning
confidence: 96%
“… 5 , 11 ETP-ALL is sensitive to cytarabine therapy and high dose cytarabine may be a good regimen for ETP-ALL. 61 , 62 FLAG-IDA regime may be a potential and beneficial schedule for ETP-ALL. 10 , 60 Therefore, after the initial induction failed, we turned to FLAG-IDA combined with sorafenib, a treatment that achieved satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…ETP-ALL/LBL has been reported with PB and BM involvement, differing from our patient’s presentation. These patients may have higher rates of central nervous system involvement, stage IV disease, remission failure, and relapse, as well as lower event-free survival and OS compared with T-ALL/LBL patients 1–7,9–13,16,17. When compared with established T-ALL/LBL prognostic markers like prednisone response and MRD, ETP status may be a stronger predictor of poorer outcome 1.…”
Section: Discussionmentioning
confidence: 99%